Royal wedding [videorecording (DVD)] - Astaire, Fred; Lawford, Peter, 1923-1984; Powell, Jane, 1929-2021-; Churchill, Sarah, 1914-1982; Donen, Stanley (Ovation Home Video, 2001)
A musical set during Princess Elizabeth's wedding to Philip Mountbatten. A brother-sister dance team go to London and get caught up in romance.